A TRIBUTE TO PROF. MUHAMMAD HAFIZULLAH - Javaid, Arshad (Journal of Postgraduate Medical Institute, 2011)
It is only appropriate that I write my first editorial for JPMI, as a tribute to my very close friend & colleague Professor Muhammad Hafizullah, who needs no introduction. He has so many facets to his personality that it is difficult to decide where to start – the caring and compassionate cardiologist who mends broken hearts, the prolific and witty writer of the regular newspaper column, the spiritual soofi whose head is shaved after umrah almost twice a year, the motivating mentor of many trainees, the active and energetic faculty member of PGMI, a dynamic chief Executive of Lady Reading Hospital or the intellectually astute and gifted Chief Editor of JPMI.